2008
DOI: 10.1038/oby.2008.142
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Eating Disorder Examination-Questionnaire for Bariatric Surgery Candidates

Abstract: Objective-Despite increasing use of the Eating Disorder Examination-Questionnaire (EDE-Q) in bariatric surgery patients, little is known about the utility and psychometric performance of this self-report measure in this clinical group. The primary purpose of the current study was to evaluate the factor structure and construct validity of the EDE-Q in a large series of bariatric surgery candidates.Methods and Procedures-Participants were 337 obese bariatric surgery candidates. Participants completed the EDE-Q a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 59 publications
2
45
0
Order By: Relevance
“…Furthermore, collapsing the original shape and weight concern subscales into one single factor is consistent with previous research on both the EDE and EDE‐Q among women with bulimic symptoms, women from an outpatient eating disorder service, female community samples, treatment seeking obese females, and adolescent girls . This notion supports a model where adolescents have difficulty in distinguishing shape and weight as separate concepts, as found previously with obese adults . Furthermore, support for separate restraint and eating concern subscales have also been provided previously …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, collapsing the original shape and weight concern subscales into one single factor is consistent with previous research on both the EDE and EDE‐Q among women with bulimic symptoms, women from an outpatient eating disorder service, female community samples, treatment seeking obese females, and adolescent girls . This notion supports a model where adolescents have difficulty in distinguishing shape and weight as separate concepts, as found previously with obese adults . Furthermore, support for separate restraint and eating concern subscales have also been provided previously …”
Section: Discussionsupporting
confidence: 87%
“…The findings support research which has failed to substantiate the EDE‐Q's original four factor structure . However, it is worth acknowledging that the original subscales were mostly reproduced within the new model, aside from the combination of the original shape and weight concern subscales.…”
Section: Discussionsupporting
confidence: 69%
“…The factor structure as originally published by Fairburn (Fairburn and Beglin, ) was not replicated in the present study, as numerous others have found (Allen et al ., ; Becker et al ., ; Hrabosky et al ., ; Peterson et al ., ). The first factor we obtained represented a mix of all the SC and WC items, except the preoccupation with weight/shape item.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hrabosky et al . () found support for an abbreviated 12‐item four‐factor scale, whereas Becker et al . () argued for the interpretation of the global EDE‐Q score as a unitary construct.…”
Section: Introductionmentioning
confidence: 99%
“…While the EDE‐Q consistently demonstrates acceptable reliability and validity, one point of weakness is in its proposed four‐factor structure, which has proven difficult to replicate. At present, ten studies have subjected EDE‐Q data to confirmatory factor analyses (CFAs) (Allen, Byrne, Lampard, Watson, & Fursland, ; Barnes, Prescott, & Muncer, ; Chan & Leung, ; Darcy, Hardy, Crosby, Lock, & Peebles, ; Franko et al, ; Grilo, Henderson, Bell, & Crosby, ; Grilo, Reas, Hopwood, & Crosby, ; Hrabosky et al, ; Penelo, Negrete, Portell, & Raich, ; White, Haycraft, Goodwin, & Meyer, ; Table ). Four studies, surveying male and female athletes and non‐athletes, Latina women, bariatric surgery patients, and schoolchildren reported indices of model fit in the acceptable range for the four‐factor model (Darcy et al, ; Franko et al, ; Hrabosky et al, ; Penelo et al, ).…”
Section: Introductionmentioning
confidence: 99%